Recurrence patterns and prognostic factors in lymphovascular space invasion-positive endometrioid endometrial cancer surgically confined to the uterus - Hanifi Sahin; Mehmet Mutlu Meydanli; Mustafa Erkan Sari; Eda Kocaman; Zeliha Firat Cuylan; Ibrahim Yalcin; Gonca Coban; Özlem Özen; Levent Sirvan; Tayfun Güngör; Ali Ayhan (Elsevier, 2019)
Objective: The purpose of this study was to determine the patterns of failure and prognostic factors for lymphovascular space invasion (LVSI)-positive endometrioid endometrial cancer (EC) patients in the setting of negative lymph nodes (LNs). Materials and methods: A multicenter, retrospective department database review was performed to identify LVSI-positive patients with disease surgically confined to the uterus at two gynecologic oncology centers in Turkey. Demographic, clinicopathological and survival data were collected. Results: We identified 185 LVSI-positivewomen with negative LNs during the study period. Fifty-five (29.7%) were classified as Stage IA, 94 (50.8%) as Stage IB, and 36 (19.5%) as Stage II. The median age at diagnosis was 59 years and the median duration of follow-up was 44 months. The total number of the recurrences was 12 (6.5%). We observed 5 (2.9%) loco-regional recurrences, 3 (1.5%) retroperitoneal failures, and 4 (2.0%) distant relapses. The 5-year progression-free survival (PFS) was 86.1% while the 5-year overall survival (OS) rate was 87.7%. Grade 3 histology (Hazard Ratio [HR] 2.9, 95% Confidence Interval [CI] 1.02-8.50; p = 0.04), cervical stromal invasion (HR 4.5, 95% CI 1.61-12.79; p = 0.004) and age ≥ 60 years (HR 5.8, 95% CI 1.62-21.32; p = 0.007) were found to be independent prognostic factors for decreased OS. Adjuvant treatment did not appear as a prognostic factor for OS even in univariate analysis. Conclusion: The recurrence rate among LVSI-positive endometrioid EC patients is low in the setting of negative LNs. However, one out of three patients with a recurrence experiences distant relapses which usually portend worse outcomes. Keywords: Endometrioid adenocarcinoma, Endometrial cancer, Recurrence, Lymphovascular space invasion, Negative lymph nodes